The Effect of Profitability and Solvency on Firm Value With Liquidity as a Moderating Variable in the Mining Sector Listed on the Indonesia Stock Exchange - Faya Pratama Kuncoro Putra; Ira Wikartika (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This paper investigates how profitability and solvency influence firm value, considering liquidity as a moderating variable within mining firms registered on the Indonesia Stock Exchange between 2022 and 2024. The dependent variable applied is firm value, quantified through the Price to Book Value (PBV). The independent components feature profitability, illustrated by Return on Assets (ROA), and solvency, illustrated by the Debt to Equity Ratio (DER), while liquidity acts as a moderating component measured using the Current Ratio (CR). The study utilizes a quantitative method alongside a purposive sampling technique, leading to a total population of 63 firms, with the final sample selected based on defined criteria. The study utilized multiple linear regression and Moderated Regression Analysis (MRA) facilitated by SPSS software. The findings suggest that profitability significantly enhances firm value, in contrast to solvency, which negatively affects firm value significantly. Moreover, liquidity is observed to moderate the scenario among solvency and firm value, yet lacks moderation the association among profitability and firm value.